Public administration : an action orientation - Denhardt, Robert B. 1942-; Denhardt, Janet Vinzant; Blanc, Tara A. (Australia : WADAWORTH/ cengage learning, 2014)
Encourages students to become active participants in public administration. This title helps readers teach how to influence the operations of public agencies - helping them learn to get involved and effect positive changes, regardless of whether they are working outside the agency as citizens or within the agency as managers.
pt.1 personal action in public organizations -- pt. 2 the political context of public administration -- pt.3 the inter organizational context of public administration -- pt.4 planning, implementation and evaluation -- pt.5 budgeting and financial management -- pt.6 the management of human resources -- pt.7 the ethics of public service -- pt.8 designing and managing organizations -- pt.9 leadership and management skills in public organizations -- pt.10 administrative reform, productivity and performance -- pt.11 opportunities for the future : globalization, democracy and the new public service
Includes bibliographical references (p. 415-428) and index.
Keywords: Public administration -- Textbooks